Consumers’ Attitude towards Digital Social Responsibility: Impacts on Electronic Word of Mouth and Purchase Intention - Wilert Puriwat; Suchart Tripopsakul (Emerging Science Journal, 2022)
Social responsibility is understood to be one of the crucial strategic responsibilities for organizations across the globe. In the digital era, firms have transformed social responsibility initiatives into digital platforms. This study aims to investigate the effects of digital social responsibility (DSR) on electronic word of mouth (eWOM) and purchase intention (PI) in the social media context. This survey research is based on 214 samples, collected via an online questionnaire as a research tool. Structural equation modelling has been used to validate the proposed hypotheses. The results show that perceived DSR has significant positive influence on consumers’ attitude (b = 0.408) and eWOM (b = 0.238). The mediation analysis indicates that consumers’ attitude partially mediates the relationship between DSR and eWOM (DE = 0.238, IE = 0.154), and fully mediates the relationship between DSR and PI (DE = 0.08, IE = 0.173). Since few previous studies have explored the impact of DSR toward eWOM and PI, our study confirms the effects of DSR on consumers’ attitudes and eWOM. This empirical study can provide managers with further understanding of the effects of DSR via social media on consumers’ attitude and eWOM. Our results should also encourage firms to implement DSR initiatives to enhance consumers’ positive attitudes and spread positive word of mouth about firms. Doi: 10.28991/ESJ-2022-06-01-05 Full Text: PDF